The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1128/aem.43.5.1133-1138.1982
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Mineralization of Trace Concentrations of Aromatic Compounds in Lake Water and Sewage Samples

Abstract: The rates of mineralization of phenol, benzoate, benzylamine, p -nitrophenol, and di(2-ethylhexyl) phthalate added to lake water at concentrations ranging from a few picograms to nanograms per milliliter were directly proportional to chemical concentration. The rates were still linear at levels of <1 pg of phenol or p -nitrophenol per ml, but it was less than the predicted value at 1.53 pg of 2,4-dichlorophenoxyacetate per ml. Mineralization of 2,4-dichlorophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 9 publications
(7 reference statements)
2
36
0
Order By: Relevance
“…This limitation was due to the inherent limit in microbial competence in dechlorinating congeners with certain Cl substitution patterns [2,10]. It is unclear whether this limit is also affected by PCB concentrations, because the microbial population or activity is often determined by substrate concentrations [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This limitation was due to the inherent limit in microbial competence in dechlorinating congeners with certain Cl substitution patterns [2,10]. It is unclear whether this limit is also affected by PCB concentrations, because the microbial population or activity is often determined by substrate concentrations [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…One obstacle in quantitative studies using I4C-labeled substances is how to define a rate constant from the nonlinear plots. The maximum rate (Boethling and Alexander, 1979) or the rate from the initial linear portion of the plots (Novick and Alexander, 1985;Rubin et al, 1982;Subba-Rao et al, 1982) have been used, and these rates were linear functions of co at low values of co with different chemicals under various conditions. The rate thus defined is probably equivalent to the rate constant k3, since the rate and the rate constant for a zero-order process are equivalent, and since k3 was also linear with low co.…”
Section: Discussionmentioning
confidence: 99%
“…However, situations are known in which mineralization of a cosubstrate occurs. For example, Rubin et al [6] found that 95% of the radioactive carbon in labeled benzoic acid and phenylacetic acid that was added in low concentrations to samples of lake water or sewage was released as 14C02. Thus, a mineralization process similar to cometabolism may occur at low substrate concentrations.…”
Section: Modes Of Biodegradationmentioning
confidence: 99%
“…Obligate oligotrophs cannot tolerate high carbon concentrations, whereas facultative oligotrophs are dormant under conditions of high carbon concentrations but are reactivated when the carbon level is reduced. In contrast, eutrophs are organisms that proliferate under conditions of high organic carbon but do not function at low organic carbon concentrations [6,7]. Thus, a chemical present at high concentrations would tend to be degraded by eutrophs but would be unaffected by oligotrophs.…”
Section: Modes Of Biodegradationmentioning
confidence: 99%
See 1 more Smart Citation